Metode Musyawarah dalam Pembelajaran Ilmu Fikih di Ma’had Aly Lirboyo Kediri - M. Ali Irsyad; Makhromi (Indonesian Journal of Humanities and Social Sciences, 2021)
This research intersects with the jurisprudence discussion at Ma'had Aly Lirboyo. Deliberation itself is a joint discussion to decide on solving a problem. This study aimed to determine the implementation of the deliberation method in learning fiqh at Ma'had 'Aly Lirboyo Kediri. The research method used is interview, observation, documentation. Data analysis was developed through qualitative descriptive analysis. While the approach used is phenomenological. In this study, most of the data were obtained directly from informants and primary data, which were then supported by secondary data sources as material for analyzing research results. The research and data analysis results obtained two types of deliberation models in learning fiqh at Ma'had 'Aly Semester II Pondok Pesantren Lirboyo Kediri; namely: first, group deliberation; second, joint deliberation.